Potential And Challenges Of The Developing Countries In Combating Global Forces In Shaping The Future Of Business: Special Reference To The Brics Countries (Trinity Journal of Management, IT & Media (TJMITM), 2014)
Business Environment, which involves both the micro and macro  environment is highly influenced by global forces. These forces have a  profound influence on the competitiveness of the business of an  economy. It is imperative that an economy or a society adapts or tries to  cope with the global forces. The niche of an economy is determined by  the adaptive nature of the economy to the global forces that shape the  nature and future of the business. The developing economies have to  take into account the global forces in curving out their path of  development. BRICS represents a group of developing and newly  industrialized countries viz., Brazil, Russia, India, China and South  Africa. It is imperative to understand the competitiveness of these four  emerging economies. In this paper, an endeavor has been made to study  the competitiveness level of these emerging economies with respect to  the challenges posed by global forces. The study is based on secondary  data from Global Competitiveness Report 2013-14, published by the  World Economic Forum. The study will provide a vivid explanation of  the importance of global forces shaping the future of business and how  the developing countries are trying to cope with the changes and  challenges posed by these forces.
Keywords: BRICS; Global Competitiveness Index; 12 pillars; Global forces Demographic dividend; Market size; Financial Institutions; Technological readiness and Innovation